The Effect of Nitrogen and Salinity on The Content of Lipid Dunaliella salina - Aziz, Hanan Abdul (Universitas Tidar, 2023)
Microalgae are micro-sized algae plants that can usually be found in fresh and marine waters. One of the marine microalgae that has the potential to be developed is Dunaliella salina because it has a fairly high nutrient content, namely 57% carbohydrates, 32% protein, and 6% lipids. Cultivation of D. salina and other microalgae in general is very dependent on several things, including nutrient content, salinity, temperature, pH, and light intensity. The nutrient that D. salina needs in large quantities is nitrogen. Besides nitrogen, salinity is also one of the other factors that also affect D. salina because D. salina is a halophilic microalgae, namely microalgae that have the ability to survive in conditions of high salt content (20–40). This study aims to determine the effect of nitrogen and salinity on lipid D content in D. salina, as well as the best nitrogen concentration and salinity concentration that can produce the highest lipids in D. salina culture. This research method is experimental. The research design used was a randomized block design (RBD) factorial pattern. There are two factors, namely factor A, which is the concentration of salinity, namely A1 = 25 ppt salinity, A2 = 30 ppt salinity, A3 = 35 ppt salinity, and A4 = 40 ppt salinity. Factor B is the nutrient content, namely B1 = NaNo 3 100g/L (control), B2 = NaNo 3 75g/L, B3 = NaNo 3 50g/L, and B4 = NaNo 3 25g/L. The results of the data analysis study showed that the highest lipids in D. salina could be detected on the 7th day in treatment M, namely 40 ppt salinity and 25g/L nitrogen concentration, which had the highest lipid yield of 0.7720%. Under low nitrogen conditions, microalgae can produce energy reserves such as lipids. The lowest lipid on day 7 was found in treatment D with a salinity of 25 ppt and a nitrogen concentration of 100 g/L, which was obtained at 0.3180%. Under high nitrogen conditions, microalgae produce few energy-reserve compounds such as lipids.